On the organization and thermal behavior of functional groups on Ti3C2 MXene surfaces in vacuum. (3rd October 2017) - Persson, Ingemar; Näslund, Lars-Åke; Halim, Joseph; Barsoum, Michel W; Darakchieva, Vanya; Palisaitis, Justinas; Rosen, Johanna; Persson, Per O Å
Abstract: The two-dimensional (2D) MXene Ti3 C2 T x is functionalized by surface groups ( T x ) that determine its surface properties for, e.g. electrochemical applications. The coordination and thermal properties of these surface groups has, to date, not been investigated at the atomic level, despite strong variations in the MXene properties that are predicted from different coordinations and from the identity of the functional groups. To alleviate this deficiency, and to characterize the functionalized surfaces of single MXene sheets, the present investigation combines atomically resolved in situ heating in a scanning transmission electron microscope (STEM) and STEM simulations with temperature-programmed x-ray photoelectron spectroscopy (TP-XPS) in the room temperature to 750 °C range. Using these techniques, we follow the surface group coordination at the atomic level. It is concluded that the F and O atoms compete for the DFT-predicted thermodynamically preferred site and that at room temperature that site is mostly occupied by F. At higher temperatures, F desorbs and is replaced by O. Depending on the O/F ratio, the surface bare MXene is exposed as F desorbs, which enables a route for tailored surface functionalization.